MAHASISWA DAN TRANSFORMASI SOSIAL PERSPEKTIF FILOSOFIS DAN AL QUR’AN - Hamdani Khaerul Fikri (UIN Mataram, 2022)
: Before talking at length about social responsibility as a student, it is necessary to first understand about the concept of students and social transformation. Because with the explanation of these two concepts at least, readers can see and identify aspects of these two concepts that are in dialogue instead of independent. Because if understood independently it will result in a disparity in the role between the two concepts. Students seen in the administrative aspect, is a person who is in the process of studying and is undergoing education in one form of college, both academic, polytechnic, high school, institute and university. Meanwhile, according to Siswoyo, students are individuals who are studying at the college level, both public and private or other institutions that are at the same level as universities.